2013
DOI: 10.5688/ajpe779194
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Work Setting Profile Factors From the Career Pathway Evaluation Program

Abstract: Objectives. To describe the work factors associated with 28 different career areas as reported by pharmacists who responded to the American Pharmacists Association (APhA) Career Pathway Evaluation Program for Pharmacy Professionals, 2012 Pharmacist Profile Survey Methods. Data from the 1,119 completed survey instruments from the 2012 Pharmacist Profile Survey were analyzed. Exploratory factor analysis was used to identify the underlying factors that best represented respondents' work setting profiles. Results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…11 Additionally, students who desire to achieve SA may consider careers in academia, a clinical practice, or social and administrative responsibilities, as well as pharmacy association management opportunities. 16 All of these may be easier to achieve after PGT. Faculty and administrators at colleges of pharmacy can develop curricular and cocurricular methods that encourage students to self-evaluate and explore their potential careers more thoroughly and with self-actualization in mind before making decisions on PGT.…”
Section: Discussionmentioning
confidence: 99%
“…11 Additionally, students who desire to achieve SA may consider careers in academia, a clinical practice, or social and administrative responsibilities, as well as pharmacy association management opportunities. 16 All of these may be easier to achieve after PGT. Faculty and administrators at colleges of pharmacy can develop curricular and cocurricular methods that encourage students to self-evaluate and explore their potential careers more thoroughly and with self-actualization in mind before making decisions on PGT.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from that survey were published as journal articles in 2003. 22,23 The profile survey was repeated during 2007 24,25 and again in 2012 26 using a web-based data collection technique. Using the previous survey instruments and findings as guides, the profile survey was updated and administered again during the summer of 2018.…”
Section: Introductionmentioning
confidence: 99%
“…, pharm industry-research & development (4.2), and health system pharmacy-inpatient (4.1) respondents. For research (including writing and travel), the highest scores were reported by pharm industryresearch & development (6.4), pharm industry-sales and liaison services (5.2), academia-social and administrative sciences (5.0), and corporate services management (4.7).For historical context,Table 4displays a comparison of the six factors identified in the 2002 survey 22 with the 10 factors identified in the 2007 survey25 , the 11 factors identified in the 2012 survey, 26 and the 11 factors identified in the 2018 survey. The 2018 findings reveal how career pathways for pharmacy professionals are evolving over time.…”
mentioning
confidence: 99%